Perilaku Konsumtif Perspektif Ekonomi Islam di Masa Pandemi Covid-19 - Tabran, Muhammad Tabran; Alma; Wahyuddin; Sirajuddin (Institut Agama Islam Negeri Parepare, 2022)
Consumptive behavior among students is influenced not only by internal factors but also actively shaped by external factors, driving an ongoing increase in purchasing and spending to fulfill their needs. From the standpoint of Islamic economics, individuals are encouraged to adopt a frugal and simple lifestyle, particularly students. This research aims to analyze the consumptive behavior of 30 students from the Faculty of Islamic Economics and Business at Alauddin State Islamic University in Makassar, considering the perspective of Islamic economics during the COVID-19 pandemic. The study employs a qualitative approach in the form of field research, utilizing data collection techniques such as interviews, observations, and documentation of the selected students. The findings reveal that the consumptive behavior of these 30 students during the COVID-19 pandemic remains relatively active. However, there are instances of impulsive purchasing, wastefulness, and a pursuit of pleasure. From the perspective of Islamic economics, consumptive behavior is deemed undesirable as it prioritizes desires over needs and leads to wasteful practices, contrary to Islamic economic principles that advocate for frugality and simplicity.